Lewicowość i socjalizm w doktrynie narodowego socjalizmu - Bankowicz, Marek (Wydawnictwo Uniwersytetu Wrocławskiego, 2011)
The article presents and substantiates a thesis that socialism — beside nationalism and racism — constituted one of the doctrinal-and political pillars of German National Socialism and of the political doctrine of Adolf Hitler. National Socialism, however, represented a peculiar version of socialism that did not fit into the internationalist tradition of class socialism. National Socialism replaced the idea of class struggle with the notion of racial struggle, put racial revolution in the place of proletarian one and identified the creation of the perfect national community of the “master race” the destiny of which is to rule the world — and not the establishment of the perfect egalitarian system which is the destiny of all mankind — as an ultimate objective. Nevertheless, National Socialism has many things in common with the main branch of socialism, including revolutionary approach, criticism of capitalism and democracy, dictatorial conception of political power, the idea of the guiding role of a party and the affirmation of force and violence as legitimate instruments of achieving political objectives.
Keywords: socjalizm; narodowy socjalizm; doktryna narodowego socjalizmu; lewicowość